2022
DOI: 10.3389/fendo.2022.989202
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center study on glucometabolic response to bariatric surgery for different subtypes of obesity

Abstract: ObjectivesTo assess the benefit of a bariatric surgery in four artificial intelligence-identified metabolic (AIM) subtypes of obesity with respect to the improvement of glucometabolism and the remission of diabetes and hyperinsulinemia.MethodsThis multicenter retrospective study prospectively collected data from five hospitals in China from 2010 to 2021. At baseline 1008 patients who underwent a bariatric surgery were enrolled (median age 31 years; median BMI 38.1kg/m2; 57.40% women) and grouped into the four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Paired sample t-test was applied to see the difference between baseline with follow-ups 1 & 2.blood glucose levels following the surgery. A similar finding was reported by Liu et al, in 202245 . They observed a median HbA1c decrease of 27.2% following bariatric surgery.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Paired sample t-test was applied to see the difference between baseline with follow-ups 1 & 2.blood glucose levels following the surgery. A similar finding was reported by Liu et al, in 202245 . They observed a median HbA1c decrease of 27.2% following bariatric surgery.…”
supporting
confidence: 91%
“…HbA1c decreased in this study, suggesting improved that loss of weight and restriction of calories may have a significant role in such outcomes. They also suggested that other causes, such as decreased inflammatory factors production from adipose tissue, raised release of hormones from the gastrointestinal tract, gut microflora changes, and alterations in the concentration of branched amino acids or bile within the circulation contribute to the improvement of HbA1c [45][46][47] [Figure 4].…”
Section: Discussionmentioning
confidence: 99%